The intermedius nerve as a confounding variable for monitoring of the free-running electromyogram. Issue 9 (September 2015) - Prell, Julian; Strauss, Christian; Rachinger, Jens; Scheller, Christian; Alfieri, Alex; Herfurth, Kirsten; Rampp, Stefan
Highlights In vestibular schwannoma patients with an identifiable intermedius nerve, the free-running EMG may show additional A-trains. A-train activity attributable to the intermedius nerve does not have a relevant clinical correlate. Thus, for interpretation of the free-running EMG, the intermedius nerve needs to be taken into account as a confounder.